Deep learning for strategic decision makers : understanding deep learning and how it produces business value - Stirrup, Jen (O'Reilly, 2017)
"Deep learning (DL) is an exciting new data technology that's creating business value for companies like Google, Yahoo, Microsoft, Amazon, Netflix, Spotify, and more. This course explains DL's core concepts, demystifies the math and science underlying the technology, and reviews its strengths, weaknesses, challenges, and risks from a strategic perspective. Business executives seeking a market-focused introduction to this technology will come away with the ability to articulate DL's core concepts and an understanding of how they fit together to produce business value."--Resource description page